Cytotoxicity Studies on Naproxen and Piroxicam Nanoformulations - Patnaik, Sandeep; Rao, K Madhusudhana; Sai, Vijay (Asian Journal of Pharmaceutical Research and Development, 2020)
Caco-2 cells were used as in vitro models to assess the cell viability characteristics of the carriers Soluplus®, Gelucire 50/13 and PVP K25 and the nanoformulations of Naproxen and Piroxicam. The assessment of cell viability was done using the tetrazolium salt based MTT assay. Gelucire 50/13 and its NFs were observed to have slightly higher cytotoxicity than PVP and Soluplus® and their respective NFs. All the NFs were observed to follow the cytotoxicity trend of the polymers. Our results show that no significant decrease in cell viability was seen until 0.01% concentration of Gelucire 50/13 for 12-h exposure. The NFs as well as the polymers alone had no significant effect on the viability of Caco-2 cells below 0.01% concentrations. The intestine has a protective mucous layer, whereas the cell culture monolayers do not. The intestinal tissues also have more capacity to recover from trauma than the cultured cells. Hence the present NFs can be expected to show lesser cytotoxicity when subjected to in vivo studies.